Managerial Knowledge Sharing Behavior in the Commercial Banking Sector - THERESIA PURBANDARI; MUJILAN MUJILAN (The Indonesian Journal of Accounting Research, 2013)
This study investigates the antecedents and consequences of knowledge sharing using a survey method. This study focuses on testing the relationship of learning organization and IT support for the knowledge sharing, innovation, and performance. The respondents are middle managers from commercial banks; however non-managers are investigated too as a comparison analysis. A component based SEM using SmartPLS is adopted to test the data. The findings indicate that managers and non-managers have different perceptions of knowledge sharing. Trust in the supervisor and other members is important for the presence of motivation to share. Middle managers need to have a clear, shared vision to consider engaging in sharing. IT support for knowledge management does not have a direct impact on knowledge sharing but it has significant direct impact on firm innovation. Overall, the findings suggest that to leverage knowledge sharing activity in the organization we need to understand the stakeholder characteristics and their job positions. Also, socialization of the IT purpose in the knowledge management context is needed.